Numerical modelling of coupled heat, moisture and salt transport in porous materials - Koniorczyk, Marcin; Gawin, Dariusz (Computer Assisted Methods in Engineering and Science; Vol 13 No 4 (2006), 2022)
A mathematical model describing coupled heat, moisture and salt transport in porous materials is presented. Salt dissolved in water can be transported due to various mechanisms: dispersion caused by the salt concentration gradient, and advection resulting from the capillary pressure gradient. The influence of salt on the physical properties of water such as density and dynamic viscosity is also considered. The isotherms of water sorption are modified to take into account both osmosis and effects of the salt presence on the surface tension and contact angle. Salt precipitation in the state of thermodynamic equilibrium between dissolved and crystallized salt is also considered. Finally, the model equations were discretized in space by means of FEM and the HMTRA-SALT software was developed. An example concerning a wall drying process was numerically solved to show the robustness of the code.